Testing the Effectiveness of Areca Catechu Seed Extract as a Stamina Booster in Laboratory Mice - Imam Samudra; Taufikur Rahman; Lisa Narulita (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Stamina is an important physiological indicator that determines the ability of organisms to sustain prolonged physical activity without excessive fatigue. Specific Background: Natural plant-based substances such as Areca catechu seeds are traditionally used as stimulants because they contain bioactive compounds including alkaloids, flavonoids, and tannins. Knowledge Gap: However, experimental evidence regarding the stamina-related physiological response to Areca catechu seed extract in controlled laboratory conditions remains limited. Aims: This study aimed to evaluate the ability of Areca catechu seed extract to increase stamina in male mice using a swimming endurance test. Results: The experiment involving five groups of mice showed that extract administration increased swimming endurance time, with the highest duration recorded at the 2 g/kg body weight dose. Novelty: The findings demonstrate a clear dose-dependent pattern of increased endurance following administration of Areca catechu seed extract. Implications: These results indicate the potential of Areca catechu extract as a natural candidate for stamina-related phytopharmaceutical development. Highlights: Higher extract dosage produced progressively longer activity duration in experimental animals. The 2 g/kg BW treatment generated the longest recorded performance time among all groups. Statistical testing confirmed measurable differences between treatment groups and untreated animals. Keywords: Areca Catechu, Areca Nut, Stamina, Mice, Swimming Endurance Test.